Influence of different types of hydrogen treatment on hydrogen retention and release from 12Kh18N10T steel - Bondarenko, M.N.; Glazunov, G.P.; Konotopskiy, A.L.; Lozin, A.V.; Moiseenko, V.E.; Aksenov, N.N.; Garkusha, I.E.; Herashchenko, S.S.; Makhlaj, V.A. (Вопросы атомной науки и техники, 2018)
Hydrogen outgassing from stainless steel was investigated after sample treatment by different plasmas: VHF/RF
pulse discharges during wall conditioning in the Uragan-2M torsatron, with RF pulse plasma heating regime in
Uragan-2M, with steady state plasma of magnetron type discharges in DSM-1 device, with pulse plasma in the
plasma accelerator QSPA Kh-50. For comparison the rate of hydrogen release from SS samples was measured after
their saturation in molecular hydrogen gas at the low pressure of ~10⁻² Torr at the room temperature. The
measurements of hydrogen release rate were carried out with thermal desorption method and mass-spectrometry. It
was observed the significant differences in hydrogen outgassing behavior for samples treated with different
hydrogen plasma. The possible reasons of distinctions in kinetics of hydrogen interaction with stainless steel are
discussed. Газовиділення водню із зразків нержавіючої сталі проводилося після обробки різною плазмою:
імпульсних розрядів УКХ/ВЧ під час чистки стінки в торсатроні Ураган-2М, у режимі нагріву плазми з ВЧімпульсом в Урагані-2М, у стаціонарній плазмі розрядів магнетронного типу в пристрої ДСМ-1 з
імпульсною плазмою, у плазмовому прискорювачі КСПП Х-50. Крім того, для порівняння
використовувалося насичення в молекулярному газоподібному водні при низькому тиску (~10⁻²Торр) та
кімнатній температурі. Вимірювання швидкості виділення водню проводилися методом термічної десорбції
за участю мас-спектрометрії. Спостерігалися істотні відмінності в характері виділення водню для зразків,
оброблених різною водневою плазмою. Обговорюються можливі причини відмінностей в кінетиці взаємодії
водню з нержавіючою сталлю. Газовыделение водорода из образцов нержавеющей стали проводилось после обработки различной
плазмой: импульсных разрядов УКВ/ВЧ во время чистки стенки в торсатроне Ураган-2М, в режиме нагрева
плазмы с ВЧ-импульсом в Урагане-2М, в стационарной плазме разрядов магнетронного типа в устройстве
ДСМ-1 с импульсной плазмой, в плазменном ускорителе КСПУ Х-50. Кроме того, для сравнения
использовалось насыщение в молекулярном газообразном водороде при низком давлении (~10⁻² Торр) и
комнатной температуре. Измерения скорости выделения водорода проводились методом термической
десорбции с участием масс-спектрометрии. Наблюдались существенные различия в характере выделения
водорода для образцов, обработанных различной водородной плазмой. Обсуждаются возможные причины
различий в кинетике взаимодействия водорода с нержавеющей сталью.